A New Cultural Concept: Literature Museum Libraries - Semra Atınç; Şenol Karadeniz (Türk Kütüphaneciliği)
Social transformations of our age reform production and consumption relations. Being social institutions, libraries are also affected by this transformation. In this respect, it is required to rehandle and improve the traditional library concept attached on public libraries in Turkey, and to diversify their current functions. The Ministry of Culture launched the Project of Literature Musem Libraries in order to contribute to literature production and literary appeal in Turkey through libraries. Besides their feature as a cultural meeting point to inspire literary life, literature museum libraries also contribute to embracing Turkey’s cultural heritage and improving cultural tourism in Turkey.